BIO-ORGANO MINERAL EFFECT ON SOIL FERTILITY, NUTRIENT UPTAKE, AND SWEET CORN (Zea mays L. saccharata) GROWTH PLANTED IN INCEPTISOLS SOILS - Restu Wulansari; Maryono Maryono; Didit Adi Darmawan; Faris Nur Fauzi Athallah; Fardian Khairul Hakim (Puslitbang tekMIRA, 2022)
Sweet corn (Zea mays L. saccharata) is a horticultural product widely consumed by Indonesian people because of its sweetness. Corn requires sufficient nutrients to grow and produce the optimal yield so that the fertilization is a determining factor in corn cultivation. Bio-organomineral fertilizer (BIOM) is a fertilizer that combines mineral, organic, and biological elements (microorganisms). This study aims to examine the effect of BIOM on growth of sweet corn, nutrient uptake, and soil fertility. Experimental design used in this research was Randomized Block Design (RBD) with nine treatments and three replications which consist of treatments control; 1 NPK; ½ BIOM; 1 BIOM; 1 NPK + ½ BIOM; 1 NPK + ¾BIOM; 1 NPK + 1 BIOM; ¾NPK + 1¼BIOM; and ¾NPK + 1½BIOM. Effect of BIOM fertilizer at 100% dosage significantly increased the plant height, stem diameter, and canopy diameter compared to the control. BIOM fertilizer had a significant effect on the N uptake, total N, P-potential, P-available, K-potential, and K- exchangeable. The fertilizer is able to provide positive results on the growth of sweet corn, so it’s more effective for the availability of nutrients needed by sweet corn plants.